Penggunaan Eufemisme sebagai Strategi Pelanggaran Maksim dalam Film The Substance - Handoko Aldianto (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2026)
Euphemistic expressions are frequently employed in communication to present unpleasant or sensitive realities in a more acceptable manner. From a pragmatic perspective, euphemisms may also serve as a means of flouting conversational maxims, enabling speakers to imply meanings indirectly rather than state them explicitly. This study investigates the use of euphemism as a maxim-flouting strategy in the film The Substance. Employing a descriptive qualitative approach, the study analyzed euphemistic utterances identified from the film screenplay by applying Grice’s Cooperative Principle and theories of euphemism. The analysis demonstrates that euphemisms are utilized to obscure, soften, or indirectly convey sensitive matters associated with aging, declining fame, concealed identity, illness, and bodily transformation. These expressions were found to involve the flouting of the maxims of quantity, quality, relation, and manner, thereby generating conversational implicatures that require audiences to infer meanings beyond the literal expressions. Furthermore, the findings indicate that euphemism contributes significantly to reinforcing the film’s major concerns, particularly those related to beauty standards, anxiety about aging, and self-identity. Accordingly, euphemism functions not merely as a politeness strategy but also as an effective pragmatic device for constructing implicit meaning in cinematic discourse.